REAL TIME PPP APPLIED TO AIRPLANE FLIGTHT TESTS - Monico, João Francisco Galera; Marques, Haroldo Antonio; Tsuchiya, Italo; Oyama, Rogerio Takeshi; Queiroz, William Robson Silva de; de Souza, Mauricio Cardoso; Wentz, Jens Peter (Boletim de Ciências Geodésicas, 2019)
The availability in real time of GNSS satellites orbits, clock corrections and code and phase biases provided the possibility of application of Real Time Precise Point Positioning (RTPPP). This paper presents the methodology concerning RTPPP and application to kinematic trajectories of airplane flight tests, but without using the carrier phase bias. So, it is PPP float solution. It requires RT positioning estimation, task that most of time presents certain difficulties due to loss of communication or of satellites during maneuvers of the airplane. However, if the corrections become unavailable for a certain period of time, the system starts using the ultra-rapid IGS orbits. The experiments were accomplished taking into account a case simulating RT and another in fact RT, but storing data and corrections for post processing. The PPP solutions obtained either simulating RT or in RT were compared against the PPP post processed solution that uses the final clock and orbit corrections. Then, statistics were generated to analyze the quality of both results. They were applied to kinematic trajectory that on average was 360 km/h, reaching about 600 km/h. The results provided accuracy better than the requisites for such cases which is of about 80 cm in height.